THE EFFECTIVENESS OF USING SCRAMBLE LEARNING MODEL TOWARD STUDENTS CREATIVE THINKING ABILITY FOR CLASS VII - Muthia Rifatuljannah; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The ability of students' creative thinking in math is still less than optimal. This study aims to determine the effectiveness of the mathematics learning model at State Junior High School (SMP Negeri) 3 Kasihan Bantul by comparing its effectiveness and the learning model used in schools. The population used is the entire class VII at SMP Negeri 3 Kasihan of 122 students. The sampling technique used is the random sampling technique. It selected class VII B as the experimental class and class VII D as the control class. The data collecting technique used is the test method. The data collection instrument in the form of a test. That is the pretest and posttest. The validity test of the instrument used is constructed validity. The instrument reliability test used is alpha Cronbach. The data analysis technique used is a prerequisite test using the normality test with a chi-square formula and homogeneity test using the bartlett formula and the hypothesis test using the t-test. Based on the result of the research, it indicates that: (1) t-test result of two parties obtained tcount > ttable, tcount = 3,837 and ttable = 2,301 or tcount > ttable, tcount = 3,837 and ttable = 2,301 with 5 % of significant level and the freedom degree is 58 which means that Ho is rejected and H1 is accepted, so there is a difference of creative thinking ability of students between the class whose learning is using scramble learning model and the class whose learning is using the scientific approach for class VII students at SMP Negeri 3 Kasihan in the academic year 2017/2018. (2) t-test results of one party obtained tcount > ttable, tcount = 3,837 and ttable = 2,002 with 5% of significant level and the freedom degree is 58 which means that Ho is rejected and H1 is accepted, so the learning mathematics using scramble is more effective than learning mathematics using a scientific approach toward the creative thinking ability for class VII Students in the second Semester atÂ  SMP Negeri 3 Kasihan Bantul in the academic year 2017/2018.â€™